The Impact of Peroxiredoxin 3 on Molecular Testing, Diagnosis, and Prognosis in Human Pancreatic Ductal Adenocarcinoma - Kakehashi, Anna; Suzuki, Shugo; Nishidoi, Yusaku; Hagihara, Atsushi; Ikenaga, Hiroko; Shiota, Masayuki; Qiu, Guiyu; Noura, Ikue; Kuwae, Yuko; Vachiraarunwong, Arpamas; Fujioka, Masaki; Gi, Min; et al. (Cancers, 2025)
Background/Objective: Pancreatic ductal adenocarcinoma (PDAC) is one of the leading causes of cancer death and tumors with an extremely poor prognosis. In the present study, novel biomarker candidates useful for the early diagnosis and prognosis of human invasive PDAC were investigated. Methods: Biomarker candidates were first selected based on the proteomic/bioinformatic and clinico-pathological analyses of 10 and 100 patients with PDAC, respectively, operated at Osaka Metropolitan University Hospital (Exp. 1). Next, the expression and secretion of the target protein and its EV mRNA were investigated in pancreatic cancer cells in vitro and in a Balb/c nude mouse model. In addition, the protein and EV mRNA levels of candidate molecules were measured in the blood serum of 36 PDAC and 10 IPMN patients, and diagnostic significance was assessed (Exp. 2). Results: A significant elevation of peroxiredoxin 3 (PRX3), a mitochondrial matrix protein, was found in PDAC via LC-Ms/Ms analysis. In Exp. 1, PRX3 overexpression was found in PDAC and PanIN lesions and was associated with a tumor infiltrative growth pattern (INFc) and poor overall 1-year patient survival. The prognostic value was significantly improved when PRX3 was combined with serum SPan-1 and DUPAN-2 markers in survival analyses. Furthermore, the PRX3 protein and its extracellular vesicle (EV: exosome and oncosome)-incorporated mRNA were secreted at detectable levels from PANC-1, MIAPaCa-2, and SW1990 cells into the blood of Balb/c nude mice bearing tumors. The overexpression of PRX3 was positively correlated with that of cancer stem cell marker CD44 variant 9 (CD44v9), P-Nrf2, and FOXO3a, as well as the generation of reactive oxygen species. In Exp. 2, a significant increase in PRX3 protein and EV mRNA was detected in the blood serum of PDAC subjects compared to IPMN patients and healthy controls. Significantly higher PRX3 protein levels were found in the IPMN group. The elevation of PRX3 EV mRNA was significantly associated with poor patient survival. Conclusions: These results indicate that PRX3 may become a novel early biomarker for PDAC diagnosis and prognosis.